KERUKUNAN UMAT BERAGAMA VS KEBEBASAN BERAGAMA DI INDONESIA - Delmus Puneri Salim (Institut Agama Islam Negeri (IAIN) Manado, 2017)
Abstract. Relations between religions have been formulated in terms of religion in Indonesia. Often interreligious relations are formulated in 'religious harmony' and often the understanding of the term is influenced by the concept of 'religious freedom'. Indonesia launched Tri Harmony in preventing people from getting caught up in unnecessary conflicts, namely Inter-Religious Harmony, Religious Harmony and Harmony between Religious People and the Government. A political formula that is practically expected to be able to manage religious people. Although this formulation is not a theological formula, this formula is intended not to be involved in conflict with one another, or so that in the religious community there is no attempt to tackle each other. However, the term religious freedom is often understood as a major part of religious harmony. Freedom of religion emphasizes the right of every citizen individually to be able to believe and practice the teachings and beliefs of a trusted religion. Both of these terms affect relations between religions in Indonesia. Keywords: Harmony, Freedom, Religion, Indonesia,. Abstrak. Relasi antar agama telah dirumuskan dalam istilah yang beragama di Indonesia. Seringkali relasi antar agama dirumuskan dalam bahasa ‘kerukunan agama’ dan sering juga pemahaman istilah tersebut dipengaruhi oleh keonsep ‘kebebasan beragama’. Indonesia mencanangkan Tri Kerukunan untuk mencegah agar orang tidak terjebak dalam konflik-konflik yang tidak perlu, yaitu Kerukunan Antar-Umat Beragama, Kerukunan Intern-Umat Beragama dan Kerukunan Antara Umat Beragama dengan Pemerintah. Suatu rumusan politik yang secara praktis diharapkan dapat mengelola umat beragama. Meskipun rumusan ini bukanlah suatu rumusan teologi, tetapi rumusan ini dimaksudkan agar tidak terlibat konflik satu sama lain, ataupun agar di dalam diri umat beragama tidak ada upaya saling menjegal. Namun demikian, istilah kebebasan beragama sering dipahami sebagai bagian utama dari kerukunan umat beragama. Kebebasan beragama menekankan hak setiap warga secara individu untuk bisa meyakini dan mengamalkan ajaran dan keyakinan agama yang dipercaya. Kedua istilah ini mempengaruhi relasi antar agama di Indonesia. Keywords: Kerukunan, Kebebasan, Beragama, Indonesia.